Atrial Natriuretic Peptide Inhibited ABCA1/G1-dependent Cholesterol Efflux Related to Low HDL-C in Hypertensive Pregnant Patients - Dong, Yubing; Lin, Yi; Liu, Wanyu; Zhang, Wei; Jiang, Yinong; Song, Wei (Frontiers in Pharmacology, 2021)
Objective It has been reported that atrial natriuretic peptide (ANP) regulates lipid metabolism by stimulating adipocyte browning, lipolysis, and lipid oxidation, and by impacting the secretion of adipokines. In our previous study, we found that the plasma ANP concentration of hypertensive disorders of pregnancy (HDP) patients was significantly increased in comparison to those of normotensive pregnancy patients. Thus, this study’s objective was to investigate the lipid profile in patients with HDP and determine the effects of ANP on the cholesterol efflux in THP-1 macrophages. Methods A total of 265 HDP patients and 178 normotensive women as the control group were recruited. Clinical demographic characteristics and laboratory profile data were collected. Plasma total triglycerides (TG), total cholesterol (TC), low-density cholesterol (LDL-C), and high-density cholesterol (HDL-C) were compared between the two groups. THP-1 monocytes were incubated with different concentrations of ANP. ATP binding cassette transporter A1 (ABCA1) and ATP binding cassette transporter G1 (ABCG1) mRNA and protein were evaluated. ABCA1- and ABCG1-mediated cholesterol efflux to apolipoprotein A-Ⅰ (apoA-Ⅰ) and HDL, respectively, were measured by green fluorescent labeled NBD-cholesterol. Natriuretic peptide receptor A (NPRA) siRNA and specific agonists of peroxisome proliferator-activated receptor-γ (PPAR-γ) and liver X receptor α (LXRα) were studied to investigate the mechanism involved. Results Plasma TG, TC, LDL-C, and LDL-C/HDL-C were significantly increased, and HDL-C was significantly decreased in the HDP group comparison to the control (all P < 0.001). ANP inhibited the expression of ABCA1 and ABCG1 at both the mRNA and protein levels in a dose-dependent manner. The functions of ABCA1- and ABCG1-mediated cholesterol efflux to apoA-I and HDL were significantly decreased. NPRA siRNA further confirmed that ANP binding to its receptor inhibited ABCA1/G1 expression through PPAR-γ/LXRα pathway. Conclusions ABCA1/G1 were inhibited by the stimulation of ANP when combined with NPRA through the PPAR-γ/LXRα pathway in THP-1 macrophages. The ABCA1/G1 mediated cholesterol efflux was also impaired by the stimulation of ANP. This may provide a new explanation for the decreased level of HDL-C in HDP patients.